Samarium-cobalt alloy throwing sheet and preparation method thereof, and samarium-cobalt magnet and preparation method thereof
Through segmented casting power control, the problems of uneven thickness and tissue differences of samarium-cobalt alloy rolls are solved, the performance consistency and yield of samarium-cobalt magnets are improved, and large-scale application of samarium-cobalt magnets is realized.
Patent Information
- Application Number
- CN202411272280.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-07
AI Technical Summary
Uneven thickness and tissue differences in samarium-cobalt alloy blades lead to poor consistency of samarium-cobalt magnets, limiting their large-scale application in samarium-cobalt magnet production.
The staged casting power control method is adopted to gradually reduce the casting power by adjusting the inclination angle of the vacuum speed condenser to maintain the temperature stability of the samarium-cobalt alloy liquid, improve the temperature gradient and columnar crystal growth power during the casting process, thereby improving the samarium-shaped crystal Thickness uniformity and tissue consistency of cobalt alloy flap.
It effectively improves the performance consistency and yield of samarium-cobalt magnets, and is suitable for large-scale applications of samarium-cobalt magnet production.
Smart Images

Figure CN119274906A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth permanent magnetic materials, and in particular to a samarium-cobalt alloy sheet and a preparation method thereof, a samarium-cobalt magnet and a preparation method thereof. Background Art
[0002] Samarium cobalt magnets have high magnetic properties, low temperature coefficient, excellent high temperature stability and corrosion resistance, and are widely used in new energy vehicles, wind power generation, energy-saving home appliances, robots and other fields. Traditional raw materials for the production of samarium cobalt magnets are mainly ingots, but they are prone to produce a lot of scraps, and the ingots are difficult to crush, which is not conducive to reducing costs and improving raw material utilization. The existing technology uses samarium cobalt alloy flakes to produce samarium cobalt magnets, which can effectively reduce the adverse effects of ingots.
[0003] However, since the SmCo alloy liquid is relatively viscous and sensitive to temperature, the temperature drop during the pouring process has a significant impact on the fluidity of the SmCo alloy liquid, resulting in uneven thickness and structural differences in the SmCo alloy flakes, which makes the performance consistency of the SmCo magnet products poor, affects the yield rate of the SmCo magnets, and further limits the large-scale application of flake materials in the production of SmCo magnets.
[0004] Therefore, there is an urgent need for a method that can improve the thickness uniformity and organizational consistency of samarium-cobalt alloy flakes to solve the problem of poor performance consistency of samarium-cobalt magnets prepared from samarium-cobalt alloy flakes. Summary of the invention
[0005] Based on this, it is necessary to provide a samarium-cobalt alloy slab and a preparation method thereof, a samarium-cobalt magnet and a preparation method thereof to address the above problems. The preparation method provided by the present invention effectively improves the thickness uniformity and structural consistency of the samarium-cobalt alloy slab, and the samarium-cobalt magnet prepared by the slab has high performance consistency and high yield, and has broad application prospects.
[0006] A method for preparing samarium-cobalt alloy flakes comprises the following steps:
[0007] The smelting raw materials are smelted to obtain samarium-cobalt alloy liquid;
[0008] The samarium-cobalt alloy liquid is poured onto a rotating spinning wheel to obtain samarium-cobalt alloy spinning sheets; the pouring power includes four levels of pouring power that decrease in sequence, wherein the first pouring power is (M / 3-20)KW to (M / 3+20)KW, the second pouring power is (M / 4-20)KW to (M / 4+20)KW, the third pouring power is (M / 5-20)KW to (M / 5+20)KW, and the fourth pouring power is (M / 6-20)KW to (M / 6+20)KW, where M represents the maximum loading mass of the vacuum quick-setting furnace, in kg.
[0009] In one embodiment, when the inclination angle of the smelting component of the vacuum rapid solidification furnace reaches an initial angle, the first pouring power is used for pouring, and as the inclination angle of the smelting component increases, the power is adjusted in sequence to the second pouring power, the third pouring power and the fourth pouring power, until the pouring is stopped when the inclination angle of the smelting component reaches 90°, wherein between two adjacent power adjustment steps, the increase value of the inclination angle of the smelting component is independently selected from 5° to 15°.
[0010] In one embodiment, when the inclination angle of the smelting assembly reaches 60° to 65°, the power is adjusted to the second pouring power;
[0011] and / or, when the inclination angle of the smelting assembly reaches 70° to 75°, adjusting the power to the third pouring power;
[0012] And / or, when the inclination angle of the smelting assembly reaches 80° to 85°, the power is adjusted to the fourth pouring power.
[0013] In one embodiment, the initial angle is 50° to 60°.
[0014] In one of the embodiments, before the pouring, the samarium-cobalt alloy liquid is allowed to stand in the vacuum rapid solidification furnace for 1 to 2 minutes, and the power is set to the first pouring power.
[0015] In one embodiment, before the pouring, the temperature of the samarium-cobalt alloy liquid is 1450°C to 1550°C.
[0016] In one embodiment, in the smelting step, according to the atomic stoichiometric formula Sm(Co 1-a-b-c Fe a Cu b Zr c ) z Weigh the smelting raw materials, and weigh 1% to 2% of the mass of the smelting raw materials as the burn-out supplementary material for smelting, of which 7.0 <z<7.8,0.2<a<0.3,0.05<b<0.1,0.01<c<0.06。
[0017] In one embodiment, the rotation speed of the belt-throwing pulley is 40 r / min to 100 r / min;
[0018] And / or, the cooling water temperature of the pulley is 5°C to 20°C;
[0019] And / or, after the pouring is completed, the samarium-cobalt alloy is spun off and cooled for 1 hour to 6 hours.
[0020] A samarium-cobalt alloy sheet is prepared by the preparation method as described above.
[0021] A method for preparing a samarium-cobalt magnet comprises the method for preparing the samarium-cobalt alloy sheet as described above.
[0022] A samarium cobalt magnet is prepared by the preparation method as described above.
[0023] The above preparation method adopts a specific pouring power for segmented pouring, which effectively ensures the temperature stability of the samarium cobalt alloy liquid during the pouring process, keeps the temperature gradient at the front of the solid-liquid interface stable, and increases the pouring power to increase the fluidity of the samarium cobalt alloy liquid, thereby increasing the driving force of columnar crystal growth during the pouring process, increasing the proportion of columnar crystals in the sheet structure, and effectively improving the thickness uniformity and organizational consistency of the samarium cobalt alloy sheet, thereby improving the performance consistency of the samarium cobalt magnet product and the yield rate, which is conducive to the large-scale application of sheet materials in the production of samarium cobalt magnets. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a cross-sectional metallographic image of the samarium-cobalt alloy sheet prepared in Example 1 of the present invention;
[0026] Figure 2 This is a cross-sectional metallographic image of the samarium-cobalt alloy sheet prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0027] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0029] After long-term and in-depth research, the applicant found that since the pouring process of the samarium-cobalt alloy liquid requires a certain amount of time, the temperature drop of the samarium-cobalt alloy liquid during this period is difficult to control, and this temperature drop will cause a large difference in the thickness of the samarium-cobalt alloy sling, and the temperature drop will cause the difference in temperature gradient when the samarium-cobalt alloy liquid solidifies, thereby causing a large difference in the organization of the samarium-cobalt alloy sling. Therefore, the thickness difference and organization difference of the samarium-cobalt alloy sling are generally synchronized. The classic organization structure of the samarium-cobalt alloy sling is: a columnar crystal organization with a certain thickness along the depth of the roller surface, and a disorderly equiaxed crystal organization extending to the free surface. When the organization of the samarium-cobalt alloy sling is a through-type columnar crystal, the difference of this organization is the smallest. Therefore, increasing the proportion of columnar crystals in the samarium-cobalt alloy sling is conducive to reducing the difference of the sling organization. At the same time, the increase in the overall thickness of the samarium-cobalt alloy sling will cause the proportion of columnar crystal organization to decrease, thereby increasing the difference of the sling organization.
[0030] Based on this, the present invention provides a method for preparing samarium-cobalt alloy flakes, comprising the following steps:
[0031] The smelting raw materials are smelted to obtain samarium-cobalt alloy liquid;
[0032] The samarium-cobalt alloy liquid is poured onto a rotating spinning wheel to obtain samarium-cobalt alloy spinning sheets; the pouring power includes four levels of pouring power that decrease in sequence, wherein the first pouring power is (M / 3-20)KW to (M / 3+20)KW, the second pouring power is (M / 4-20)KW to (M / 4+20)KW, the third pouring power is (M / 5-20)KW to (M / 5+20)KW, and the fourth pouring power is (M / 6-20)KW to (M / 6+20)KW, where M represents the maximum loading mass of the vacuum quick-setting furnace, in kg.
[0033] It can be understood that when the inclination angle of the smelting component of the vacuum rapid solidification furnace reaches the initial angle, the power is set to the first pouring power to start pouring. The first pouring power is the initial pouring power. Under this initial pouring power, the fluidity of the samarium-cobalt alloy liquid is effectively improved, the temperature gradient is enhanced, and the proportion of columnar crystals in the sheet-swinging structure is increased. At the same time, it avoids damage to the smelting component due to excessive power, which is beneficial to increase the service life of the smelting component and improve safety. After the start of pouring, after pouring for a period of time at the first pouring power, as the inclination angle of the smelting component increases, the power is adjusted to the second pouring power, the third pouring power and the fourth pouring power in sequence for a period of time until the inclination angle of the smelting component reaches 90° and the pouring is stopped.
[0034] The above-mentioned preparation method adopts a specific pouring power for segmented pouring, and gradually reduces the pouring power as the inclination angle of the smelting component in the vacuum rapid solidification furnace increases, thereby effectively ensuring the temperature stability of the samarium cobalt alloy liquid during the pouring process, which is beneficial to maintaining the temperature gradient at the front of the solid-liquid interface at the temperature state under the initial pouring power. Increasing the pouring power can increase the fluidity of the samarium cobalt alloy liquid, thereby increasing the driving force for the growth of columnar crystals during the pouring process, increasing the proportion of columnar crystals in the sheet structure, and effectively improving the thickness uniformity and organizational consistency of the samarium cobalt alloy sheet, thereby improving the performance consistency of the samarium cobalt magnet product, improving the yield rate, and facilitating the large-scale application of sheet materials in the production of samarium cobalt magnets.
[0035] It should be noted that the vacuum rapid setting furnace used in the present invention is a commonly used device in the field. The present invention has no special restrictions on the maximum loading mass M (kg) of the vacuum rapid setting furnace, for example, 400kg, 500kg, 600kg, 700kg, etc. are all possible; the pouring power and the maximum loading mass M of the vacuum rapid setting furnace are only quantitative conversions, and do not involve unit conversions.
[0036] It can be understood that the smelting assembly and the belt-throwing wheel of the present invention are both commonly used devices in the art, and the present invention has no special limitations on this. For example, the smelting assembly of the present invention can be a crucible, etc., and the belt-throwing wheel of the present invention can be a copper roller, etc.
[0037] Specifically, in the smelting step, according to the atomic stoichiometric formula Sm(Co 1-a-b-c Fe a Cu b Zr c ) z Weigh the smelting raw materials, and weigh 1% to 2% of the mass of the smelting raw materials as the burn-out supplementary material for smelting, of which 7.0 <z<7.8,0.2<a<0.3,0.05<b<0.1,0.01<c<0.06。
[0038] More specifically, the raw materials are added into a vacuum melting and rapid solidification furnace in the order of iron, cobalt, copper, zirconium and samarium. After vacuuming and preheating and exhausting, vacuuming is continued, inert gas is introduced, and the melting power is set for melting. Preferably, when green light appears on the surface of the samarium-cobalt alloy liquid, a thermocouple is used to contact the alloy liquid to measure its temperature.
[0039] Specifically, the temperature of the samarium-cobalt alloy liquid is 1450°C to 1550°C.
[0040] In one embodiment, before the pouring, the samarium-cobalt alloy liquid is allowed to stand in the vacuum rapid setting furnace for 1 to 2 minutes, and the power is set to the first pouring power so that the temperature of the samarium-cobalt alloy liquid is maintained at the temperature when the smelting is completed during the standing period. After standing, the smelting assembly in the vacuum rapid setting furnace is adjusted to the initial angle, and pouring is started with the first pouring power.
[0041] In order to further improve the temperature stability of the samarium-cobalt alloy liquid during the pouring process, and thereby improve the thickness uniformity and structural consistency of the samarium-cobalt alloy sheet, between two adjacent power adjustment steps, the increase value of the inclination angle of the smelting component is preferably independently 5° to 15°, including but not limited to any point value among 5°, 6°, 7°, 9°, 10°, 12°, 13°, 15° or the range value between any two thereof.
[0042] It can be understood that when the pouring power is set to the first pouring power, the second pouring power, the third pouring power, and the fourth pouring power, the corresponding inclination angles of the smelting component are A1, A2, A3, and A4, respectively, wherein the difference between A2 and A1, the difference between A3 and A2, and the difference between A4 and A3 are each independently selected from 5° to 15°, and the above three differences may be the same or different.
[0043] The above A1 is the initial angle. The present invention has no special limitation on the initial angle for pouring the smelting assembly. According to the loading mass of the samarium-cobalt alloy liquid, the initial angle is preferably 50° to 60°.
[0044] In one embodiment, when the inclination angle of the smelting component reaches 60° to 65°, the power is adjusted to the second pouring power, that is, A2 includes but is not limited to any point value of 60°, 61°, 62°, 63°, 64°, 65° or any range value between two thereof. It can be understood that when the inclination angle of the smelting component is between A1 and A2, the first pouring power is used for pouring.
[0045] In one embodiment, when the inclination angle of the smelting component reaches 70° to 75°, the power is adjusted to the third pouring power, that is, A3 includes but is not limited to any point value of 70°, 71°, 72°, 73°, 74°, 75° or any range value between two thereof. It can be understood that when the inclination angle of the smelting component is between A2 and A3, the second pouring power is used for pouring.
[0046] In one embodiment, when the inclination angle of the smelting component reaches 80° to 85°, the power is adjusted to the fourth pouring power, that is, A4 includes but is not limited to any point value of 80°, 81°, 82°, 83°, 84°, 85° or any range value between two thereof. It can be understood that when the inclination angle of the smelting component is between A3 and A4, the third pouring power is used for pouring, and when the inclination angle of the smelting component is between A4 and 90°, the fourth pouring power is used for pouring.
[0047] In order to further improve the thickness uniformity of the samarium-cobalt alloy sling, and increase the proportion of columnar crystals in the samarium-cobalt alloy sling, so as to further improve the organizational consistency of the sling, the rotation speed of the sling pulley is preferably 40 r / min to 100 r / min.
[0048] In one embodiment, the cooling water temperature of the pulley is 5°C to 20°C.
[0049] Specifically, the samarium-cobalt alloy sheet is cooled for 1 hour to 6 hours, and water cooling or air cooling can be used in combination with water cooling.
[0050] It should be noted that the above pouring can be done manually or automatically, and the present invention has no special restrictions on this. In order to further improve the uniformity of the pouring speed, the present invention preferably uses automatic pouring.
[0051] The present invention also provides a samarium-cobalt alloy sheet obtained by the above-mentioned preparation method. The samarium-cobalt alloy sheet has high thickness concentration, a high proportion of columnar crystals in the structure, and high structural consistency, which is conducive to improving the performance consistency of the samarium-cobalt magnet product obtained therefrom.
[0052] Specifically, the thickness of different batches of samarium-cobalt alloy flakes prepared by the above preparation method is selected from (h-0.05) mm to (h+0.05) mm, where h is the average thickness of different batches of samarium-cobalt alloy flakes, and has high thickness uniformity.
[0053] The present invention also provides a method for preparing a samarium cobalt magnet, including the above-mentioned preparation method. The method for preparing a samarium cobalt magnet is conducive to improving the thickness uniformity and organizational consistency of samarium cobalt alloy slabs, thereby obtaining a samarium cobalt magnet product with high performance consistency and high yield, effectively reducing production costs and improving production efficiency. The preparation method is suitable for large-scale application of slabs in the production of samarium cobalt magnets.
[0054] Specifically, the method for preparing the samarium cobalt magnet also includes the following steps:
[0055] The samarium-cobalt alloy flakes are subjected to mechanical crushing and air-grinding treatment to obtain samarium-cobalt magnetic powder;
[0056] The samarium cobalt magnetic powder is mixed with an antioxidant, and then subjected to magnetic field molding and isostatic pressing to obtain a samarium cobalt blank;
[0057] The samarium cobalt blank is subjected to sintering, solid solution, cooling and aging treatment to obtain a samarium cobalt magnet.
[0058] In one embodiment, the particle size of the samarium-cobalt alloy flakes after mechanical crushing is 20 μm to 300 μm.
[0059] In one embodiment, the classifying rotation speed of the jet mill is 3500 r / min to 4500 r / min.
[0060] In one embodiment, the particle size of the samarium cobalt magnetic powder after the jet milling treatment is 4 μm to 6 μm.
[0061] Preferably, the weight fraction of the antioxidant in the mixed powder obtained by mixing the powders is 1‰ to 5‰, the antioxidant is selected from zinc stearate, calcium stearate, etc., and the mixing time is 1h to 4h.
[0062] Specifically, the magnetic field intensity of the magnetic field molding is 2T, the isostatic pressing pressure is 150MPa to 280MPa, and the holding time is 10min to 20min.
[0063] In one embodiment, the sintering temperature is 1180°C to 1220°C, the holding time is 2h to 4h, the solution temperature is 1150°C to 1180°C, the holding time is 2h to 10h, and then it is rapidly cooled to room temperature.
[0064] Specifically, during the aging treatment, the steel is kept at 800°C to 850°C for 5 to 20 hours, then cooled to 400°C at a rate of 0.5°C / min to 1°C / min, kept for 2 to 10 hours, and then cooled to below 80°C before being taken out of the furnace.
[0065] In the above preparation method, the processes of powder making, molding, sintering and aging treatment can adopt conventional processes in the field, without adding steps or changing the formula. The operation is simple and easy to control, and it is suitable for promotion in large-scale production.
[0066] A samarium cobalt magnet prepared by the preparation method as described above has high performance consistency, high yield rate and broad application prospects.
[0067] Hereinafter, the samarium-cobalt alloy sheet and its preparation method, the samarium-cobalt magnet and its preparation method will be further described through the following specific examples.
[0068] Example 1
[0069] According to the chemical atomic formula of samarium-cobalt alloy Sm(Co 0.68 Fe 0.22 Cu 0.075 Zr 0.025 ) 7.2 Weigh the corresponding mass of raw materials, and add 2% more samarium as burn-off supplementary material, with a total mass of 430kg, and add them into a vacuum melting and rapid solidifying furnace with a maximum loading mass M of 600kg in the order of iron, cobalt, copper, zirconium and samarium; evacuate the vacuum melting and rapid solidifying furnace to 7.0Pa, and then preheat for 25 minutes to exhaust, set the power to 210KW, and continue to evacuate to 5.0Pa after preheating, fill with argon to 0.03MPa, adjust the power to 450KW for melting, and when green light appears on the surface of the alloy liquid, use a thermocouple to contact the alloy liquid to measure its temperature, which is 1500℃.
[0070] The power was adjusted to 190KW. After standing for 1.5 minutes, the crucible was tilted for pouring through an automatic pouring program, wherein the rotation speed of the water-cooled copper roller was 50r / min, the temperature of the copper roller cooling water was 6°C, the initial tilt angle of the crucible was 55°, and pouring was started with a first pouring power of 190KW. When the tilt angle of the crucible reached 60°, the power was adjusted to a second pouring power of 160KW. When the tilt angle of the crucible reached 70°, the power was adjusted to a third pouring power of 130KW. When the tilt angle of the crucible reached 85°, the power was adjusted to a fourth pouring power of 100KW. When the tilt angle of the crucible reached 90°, the intermediate frequency was turned off and the power was adjusted to 0. The pouring was stopped. After cooling for 4 hours, the flakes were taken out of the furnace to obtain samarium-cobalt alloy flakes.
[0071] Example 2
[0072] According to the chemical atomic formula of samarium-cobalt alloy Sm(Co 0.68 Fe 0.22 Cu 0.075 Zr 0.025 ) 7.5Weigh the corresponding mass of raw materials, and add 2% more samarium as burn-off supplementary material, with a total mass of 460kg, and add them into a vacuum melting and rapid solidifying furnace with a maximum loading mass M of 600kg in the order of iron, cobalt, copper, zirconium and samarium; evacuate the vacuum melting and rapid solidifying furnace to 7.0Pa, then preheat for 25 minutes to exhaust, set the power to 210KW, and continue to evacuate to 5.0Pa after preheating, fill with argon to 0.03MPa, adjust the power to 450KW for melting, and when green light appears on the surface of the alloy liquid, use a thermocouple to contact the alloy liquid to measure its temperature, which is 1480℃.
[0073] The power is adjusted to 220KW. After standing for 2 minutes, the crucible is tilted for pouring through the automatic pouring program, wherein the rotation speed of the water-cooled copper roller is 40r / min, the temperature of the copper roller cooling water is 10°C, the initial tilt angle of the crucible is 50°, and pouring is started with the first pouring power of 220KW. When the tilt angle of the crucible reaches 65°, the power is adjusted to the second pouring power of 170KW. When the tilt angle of the crucible reaches 75°, the power is adjusted to the third pouring power of 140KW. When the tilt angle of the crucible reaches 80°, the power is adjusted to the fourth pouring power of 90KW. When the tilt angle of the crucible reaches 90°, the intermediate frequency is turned off and the power is adjusted to 0. The pouring is stopped. After cooling for 5 hours, the flakes are taken out of the furnace to obtain samarium-cobalt alloy flakes.
[0074] Example 3
[0075] According to the chemical atomic formula of samarium-cobalt alloy Sm(Co 0.68 Fe 0.22 Cu 0.075 Zr 0.025 ) 7.2 Weigh the corresponding mass of raw materials, and add 2% more samarium as burn-off supplementary material, with a total mass of 400kg, and add them into a vacuum melting and rapid solidifying furnace with a maximum loading mass M of 600kg in the order of iron, cobalt, copper, zirconium and samarium; evacuate the vacuum melting and rapid solidifying furnace to 7.0Pa, and then preheat for 25 minutes to exhaust, set the power to 210KW, and continue to evacuate to 5.0Pa after preheating, fill with argon to 0.03MPa, adjust the power to 450KW for melting, and when green light appears on the surface of the alloy liquid, use a thermocouple to contact the alloy liquid to measure its temperature, which is 1520℃.
[0076] The power was adjusted to 190KW. After standing for 2 minutes, the crucible was tilted for pouring through the automatic pouring program, wherein the rotation speed of the water-cooled copper roller was 80r / min, the temperature of the copper roller cooling water was 15°C, the initial tilt angle of the crucible was 58°, and pouring was started with a first pouring power of 180KW. When the tilt angle of the crucible reached 65°, the power was adjusted to a second pouring power of 130KW. When the tilt angle of the crucible reached 70°, the power was adjusted to a third pouring power of 100KW. When the tilt angle of the crucible reached 85°, the power was adjusted to a fourth pouring power of 80KW. When the tilt angle of the crucible reached 90°, the intermediate frequency was turned off and the power was adjusted to 0. The pouring was stopped. After cooling for 3.5 hours, the flakes were taken out of the furnace to obtain samarium-cobalt alloy flakes.
[0077] Comparative Example 1
[0078] The difference between Comparative Example 1 and Example 1 is that the initial tilt angle of the crucible is 55°, and pouring is started with a first pouring power of 150KW, until the tilt angle of the crucible reaches 60°, the power is adjusted to a second pouring power of 130KW, until the tilt angle of the crucible reaches 70°, the power is adjusted to a third pouring power of 100KW, until the tilt angle of the crucible reaches 85°, the power is adjusted to a fourth pouring power of 90KW, until the tilt angle of the crucible reaches 90°, the intermediate frequency is turned off and the power is adjusted to 0, the pouring is stopped, and the crucible is taken out of the furnace after cooling for 4 hours to obtain samarium cobalt alloy flakes.
[0079] Comparative Example 2
[0080] The difference between Comparative Example 2 and Example 1 is that the initial tilt angle of the crucible is 55°, and pouring is started with a first pouring power of 190KW, until the tilt angle of the crucible reaches 60°, the power is adjusted to a second pouring power of 120KW, until the tilt angle of the crucible reaches 70°, the power is adjusted to a third pouring power of 90KW, until the tilt angle of the crucible reaches 85°, the power is adjusted to a fourth pouring power of 70KW, until the tilt angle of the crucible reaches 90°, the intermediate frequency is turned off and the power is adjusted to 0, the pouring is stopped, and the crucible is taken out of the furnace after cooling for 4 hours to obtain samarium cobalt alloy flakes.
[0081] Comparative Example 3
[0082] The difference between Comparative Example 3 and Example 1 is that during the pouring process, the pouring power is always 170KW.
[0083] Application Examples
[0084] The samarium cobalt magnet pieces of all the embodiments and comparative examples were placed in a hammer crusher for crushing, and then zinc stearate with a mass fraction of 3‰ was added to the crushed powder and mixed for 2 hours. After that, the powder was sent to a jet mill for further crushing. The jet mill separation speed was 4000r / min to obtain samarium cobalt magnetic powder with a particle size of 4.6μm.
[0085] The samarium cobalt magnetic powder is oriented and pressed into shape with a magnetic field strength of 2T, and then is isostatically pressed with a pressure of 250MPa for 10 minutes to obtain a samarium cobalt blank.
[0086] The samarium cobalt blank was pre-sintered at 1150°C for 0.5h, then sintered at 1200°C for 3h, cooled to 1170°C for solution treatment, kept warm for 2h and quickly air-cooled to room temperature; the solution-treated blank was kept at 830°C for 10h, then slowly cooled to 400°C at a rate of 0.7°C / min, kept warm for 4h, and then slowly cooled to below 80°C in the furnace to obtain the samarium cobalt magnet after being taken out of the furnace.
[0087] Ten pieces of samarium-cobalt alloy sheets prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were respectively taken, and the thickness of the sheets was measured with a micrometer. The results are shown in Table 1.
[0088] Table 1
[0089]
[0090] Five samples of samarium cobalt magnets prepared in each of Application Example 1 and Comparative Example 1 were taken for magnetic property testing. The test results are shown in Table 2.
[0091] Table 2
[0092]
[0093] According to the results in Table 1, the thickness range of the samarium cobalt magnet sheets prepared in all embodiments of the present invention is relatively concentrated, which is conducive to improving the consistency of the sheets, while the thickness range of the samarium cobalt magnet sheets prepared in the comparative example is relatively dispersed, and the thickness uniformity is relatively low. At the same time, the samarium cobalt alloy sheets with the thickness closest to the average thickness among the different batches prepared in Example 1 are selected, and the metallographic image of the cross section is as follows: Figure 1 As shown, it can be seen that the proportion of columnar crystals in the whole cross section is about 80%. The proportion of columnar crystals in the slice is high, and the consistency of the organization is high, which is conducive to enhancing the orientation of the samarium cobalt magnet obtained therefrom, and improving the remanence and magnetic energy product. The samarium cobalt alloy slices with the thickness closest to the average thickness among the different batches prepared in Comparative Example 1 are selected, and the metallographic image of the cross section is as follows Figure 2As shown, it can be seen that the proportion of columnar crystals in the entire cross section in the slat is about 40%. In addition, according to the results in Table 2, the remanence and magnetic properties of the samarium cobalt magnets prepared in all application examples are higher than those of the samarium cobalt magnets in all application comparison examples, and the remanence, magnetic energy product and knee coercive force values of the samarium cobalt magnets in the application examples are more concentrated and uniform than those of the samarium cobalt magnets in the application comparison examples, and the performance consistency is good.
[0094] In summary, the preparation method provided by the present invention effectively improves the thickness uniformity and organizational consistency of the samarium-cobalt alloy sheet. The samarium-cobalt magnets made from the sheet have high performance consistency and high yield, and have broad application prospects.
[0095] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0096] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing samarium-cobalt alloy flakes, characterized in that: The preparation method comprises the following steps: The smelting raw materials are smelted to obtain samarium-cobalt alloy liquid; The samarium-cobalt alloy liquid is poured onto a rotating spinning wheel to obtain samarium-cobalt alloy spinning sheets; the pouring power includes four levels of pouring power that decrease in sequence, wherein the first pouring power is (M / 3-20)KW to (M / 3+20)KW, the second pouring power is (M / 4-20)KW to (M / 4+20)KW, the third pouring power is (M / 5-20)KW to (M / 5+20)KW, and the fourth pouring power is (M / 6-20)KW to (M / 6+20)KW, where M represents the maximum loading mass of the vacuum quick-setting furnace, in kg.
2. The method for preparing samarium-cobalt alloy flakes according to claim 1, characterized in that: When the inclination angle of the smelting component in the vacuum rapid solidification furnace reaches an initial angle, the first pouring power is used for pouring, and as the inclination angle of the smelting component increases, the power is adjusted in sequence to the second pouring power, the third pouring power and the fourth pouring power, until the pouring is stopped when the inclination angle of the smelting component reaches 90°, wherein between two adjacent power adjustment steps, the increase value of the inclination angle of the smelting component is independently selected from 5° to 15°.
3. The method for preparing samarium-cobalt alloy flakes according to claim 2, characterized in that: When the inclination angle of the smelting assembly reaches 60° to 65°, the power is adjusted to the second pouring power; and / or, when the inclination angle of the smelting assembly reaches 70° to 75°, adjusting the power to the third pouring power; And / or, when the inclination angle of the smelting assembly reaches 80° to 85°, the power is adjusted to the fourth pouring power.
4. The method for preparing samarium-cobalt alloy flakes according to claim 2, characterized in that: The initial angle is 50° to 60°.
5. The method for preparing samarium-cobalt alloy flakes according to claim 1, characterized in that: Before the pouring, the samarium-cobalt alloy liquid is allowed to stand in the vacuum rapid solidification furnace for 1 to 2 minutes, and the power is set to the first pouring power.
6. The method for preparing samarium-cobalt alloy flakes according to claim 1, characterized in that: In the smelting step, according to the atomic stoichiometric formula Sm(Co 1-a-b-c Fe a Cu b Zr c ) z Weigh the smelting raw materials, and weigh 1% to 5% of the mass of the smelting raw materials as the burn-out supplementary material for smelting, of which 7.0 <z<8.0,0.2<a<0.4,0.05<b<0.1,0.01<c<0.06; And / or, before the pouring, the temperature of the samarium-cobalt alloy liquid is 1450°C to 1550°C.
7. The method for preparing samarium-cobalt alloy flakes according to claim 1, characterized in that: The rotation speed of the belt-throwing pulley is 40 r / min to 100 r / min; And / or, the cooling water temperature of the pulley is 5°C to 20°C; And / or, after the pouring is completed, the samarium-cobalt alloy is spun off and cooled for 1 hour to 6 hours.
8. A samarium-cobalt alloy flake produced by the method according to any one of claims 1 to 7.
9. A method for preparing a samarium cobalt magnet, characterized in that: The preparation method includes the preparation method of the samarium-cobalt alloy flakes as described in any one of claims 1 to 7.
10. A samarium cobalt magnet prepared by the preparation method according to claim 9.